Evaluation of enzymatic antioxidant activity and reproductive hormones near and after lambing in pregnant ewes - Abbas, M. F.; Alsalim, H. A.; Hasan, N. S.; Abbas, H. R. (Diponegoro University, 2024)
The current study examined the levels of antioxidants superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione (GSH), and Malondialdehyde (MDA) and repro ductive hormones (progesterone, estrogen, and cortisol) in pregnant local breed ewes and after lambing in the Basrah governorate. Twenty ewes were used in this study from several fields in the Basrah gov ernorate. Blood sample collection was done in three different periods, pre-lambing, immediately after lambing, and two weeks after lambing. The result showed a significant decrease (p<0.05) in SOD, CAT, and GSH-px activity before and during lambing compared to after lambing. The results also con firmed a significant increase (p<0.05) in the level of GSH pre and during lambing compared to after lambing. While evaluating, the level of MDA revealed a significant increase (p<0.05) in its level dur ing lambing compared to two weeks after lambing. Hormonal analysis showed a significant increase (p<0.05) in the levels of cortisol and estradiol pre and during lambing compared to after lambing, with a significant decrease (p<0.05) in the levels of progesterone after lambing compared to before lambing. This study concluded that during lambing, ewes were under stress factors, and an internal mechanism represented by enzymatic antioxidants like SOD, CAT, and GSH-Px acted actively during this period to neutralize the side effects of stress.